Growth characteristics of human juvenile, adult and murine fibroblasts: a comparison of polymer wound dressings. (2nd October 2020) - Gögele, Clemens; Schulze-Tanzil, Gundula; Kokozidou, Maria; Gäbel, Christiane; Billner, Moritz; Reichert, Bert; Bodenschatz, Karl
Abstract : Objective: Fibroblasts are important for the successful healing of deep wounds. However, the influence exerted by Cuticell, a natural polymer on fibroblasts and by the synthetic polymer, Suprathel, made of poly-L-lactic acid, is not sufficiently characterised. This study compared the survival and growth characteristics of human juvenile and adult dermal fibroblasts as well as murine fibroblast cell line L929, on a natural polymer with those of a synthetic polymer using different culture models. Method: Murine, juvenile and adult human fibroblasts were seeded on both the natural and synthetic polymers using statical slide culture or the medium air interface and dynamical rotatory culture. Cell adherence, viability, morphology and actin cytoskeleton architecture were monitored for 1–7 days. Biomaterial permeability was checked with a previously established diffusion chamber. Results: The majority of the murine and adult human fibroblasts survived in slide and rotatory cultures on both wound dressings. The fibroblasts seeded on the synthetic polymer exhibited phenotypically a typical spread shape with multiple cell adhesion sites earlier than those on the natural polymer. The highest survival rates in all tested fibroblast species over the entire observation time were detected in rotatory culture (mean: >70%). Nevertheless, it led to cell-cluster formation on both materials. In the medium air interface culture, few adult fibroblasts adhered and survived until the seventh day of culture on both the natural and synthetic polymers, and no viable juvenile and L929 fibroblasts could be found by day seven. Apart from a significant higher survival rate of L929 in slide culture on the natural polymer compared with the synthetic polymer at the end of the culturing period (p<0.0001), and a higher cell survival of L929 on the natural polymer in medium air interface culture, only minor differences between both materials were evident. This suggested a comparable cytocompatibility of both materials. Permeability testing revealed slightly higher permeance of the natural polymer compared with the synthetic polymer. Conclusion: Cell survival rates depended on the culture system and the fibroblast source. Nevertheless, the juvenile skin fibroblasts were the most sensitive. This observation suggests that wound dressings used in treating children should be tested beforehand with juvenile fibroblasts to ensure the dressing does not compromise wound healing. Future experiments should also include the response of compromised fibroblasts, for example, from burn patients.